Repairing Play A Black Phenomenology - Trammell, Aaron (Playful Thinking, 2022)
A provocative study that reconsiders our notion of play-and how its deceptively wholesome image has harmed and erased people of color.Contemporary theorists present play as something wholly constructive and positive. But this broken definition is drawn from a White European philosophical tradition that ignores the fact that play can, and often does, hurt. In fact, this narrow understanding of play has been complicit in the systemic erasure of Black, Indigenous, and People of Color (BIPOC) from the domain of leisure. In this book, Aaron Trammell proposes a corrective: a radical reconsideration of play that expands its definition to include BIPOC suffering, subjugation, and taboo topics such as torture. As he challenges and decolonizes White European thought, Trammell maps possible ways to reconcile existing theories with the fact that play is often hurtful and toxic.Trammell upends current notions by exploring play's function as a tool in the subjugation of BIPOC. As he shows, the phenomenology of play is a power relationship. Even in innocent play, human beings subtly discipline each other to remain within unspoken rules. Going further, Trammell departs from mainstream theory to insist that torture can be play. Approaching it as such reveals play's role in subjugating people in general and renders visible the long-ignored experiences of BIPOC. Such an inclusive definition of play becomes a form of intellectual reparation, correcting the notion that play must give pleasure while also recasting play in a form that focuses on the deep, painful, and sometimes traumatic depths of living.